The penguin book of Japanese short stories - Rubin, Jay, 1941-; Rubin, Jay, 1941-
"This fantastically varied and exciting collection celebrates the art of the Japanese short story, from its origins in the nineteenth century to the remarkable practitioners writing today. Edited by acclaimed translator Jay Rubin, who has himself freshly translated some of the stories, and with an introduction by Haruki Murakami, this book is a revelation. Stories by writers already well known to English-language readers are included-like Tanizaki, Akutagawa, Murakami, Mishima, Kawabata, and Yoshimoto-as well as many surprising new finds. From Yuko Tsushima's "Flames" to Yuten Sawanishi's "Filling Up with Sugar" to Shin'ichi Hoshi's "Shoulder-Top Secretary" to Banana Yoshimoto's "Bee Honey," The Penguin Book of Japanese Short Stories is filled with fear, charm, beauty, and comedy." -- Publisher's description